Omicron related COVID-19 prevention and treatment measures for patients with hematological malignancy and strategies for modifying hematologic treatment regimes - Guo, Wenjing; Zheng, Yizhou; Feng, Sizhou (Frontiers in Cellular and Infection Microbiology, 2023)
The Omicron variant of SARS-CoV-2 has rapidly become the dominant strain worldwide due to its high transmissibility, although it appears to be less pathogenic than previous strains. However, individuals with hematological malignancy (HM) and COVID-19 remain susceptible to severe infection and mortality, especially those with chronic lymphocytic leukemia (CLL) and those undergoing chimeric antigen receptor T-cell (CAR-T) treatment. Hematologists should thoroughly assess the severity of the patient’s hematological disease and the potential risk of SARS-CoV-2 infection before initiating chemotherapy or immunosuppressive treatment. Vaccination and booster doses are strongly recommended and patients with a poor vaccine response may benefit from long-acting COVID-19 neutralizing monoclonal antibodies (such as Evusheld). Early use of small molecule antiviral drugs is recommended for managing mild COVID-19 in HM patients and those with severe immunodeficiency may benefit from SARS-CoV-2 neutralizing monoclonal antibody therapy and high-titer COVID-19 convalescent plasma (CCP). For moderate to severe cases, low-dose glucocorticoids in combination with early antiviral treatment can be administered, with cytokine receptor antagonists or JAK inhibitors added if the condition persists or worsens. In the treatment of hematological malignancies, delaying chemotherapy is preferable for CLL, acute leukemia (AL), and low-risk myelodysplastic syndrome (MDS), but if the disease progresses, appropriate adjustments in dosage and frequency of treatment are required, with the avoidance of anti-CD20 monoclonal antibody, CAR-T and hematopoietic stem cell transplantation (HSCT). Patients with chronic myelocytic leukemia (CML) and myeloproliferative neoplasms (MPNs) can continue current treatment. What’s more, non-drug protective measures, the development of new vaccines and antiviral drugs, and monitoring of mutations in immunocompromised populations are particularly important.